(untitled) (Research, Society and Development, 2020)
The sunflower is an oleaginous and its cultivation is associated with the production of edible oil, biodiesel, ornamentation, animal feed. The quantification of the genetic variability of sunflower can be evaluated based on its yield, which is in function of several morphological characteristics. The purpose of this study was to estimate the phenotypic dissimilarity of sunflower genotypes through morphological characteristics. The work was conducted in the experimental area of the Empresa Mato-Grossense de Pesquisa, Assistência e Extensão Rural, in Cáceres-MT, with random block design with four repetitions. Evaluating the following characteristics: beginning of flowering, physiological maturation, height of plants, curvature of the stem, size of the chapter and weight of a thousand aquenes. The phenotypic dissimilarity between the nine genotypes was evaluated based on the Generalized Distance of Mahalanobis, and using the grouping analyses of UPGMA and Tocher, Canonical Variables and Relative Importance of Characters using the Genes program. Significant differences were found by the F test at 1% probability, for all characteristics evaluated demonstrating the existence of phenotypic dissimilarity for the genotypes based on the six morphological characteristics. The AGUARÁ 06 genotype presented the greatest genetic distance being the most dissimilar and can be used for possible crosses. The characteristics beginning of flowering and physiological maturation were the most contributors to obtain phenotypic dissimilarity.